MEDICAL USE OF VITAMINS AND ANTI-VITAMINS - Keldiyorova Farangiz Navruz qizi; Shahnoza Odilova (Modern American Journals, 2025)
The clinical use of vitamins and anti-vitamins is central to the prevention, treatment, and biochemical mediation of disease in humans. Vitamins are micronutrients that play a role in a wide range of physiological functions, while anti-vitamins, whose role involves antagonizing the action of vitamins, have therapeutic uses in disease states resulting from hypervitaminosis and cancer. This review considers the medical use of each of the vitamins in clinical practice, the modes of action and uses of the anti-vitamins, and the therapeutic balance for safe treatment.
Keywords: Vitamins, anti-vitamins, micronutrients, deficiency, hypervitaminosis, therapeutic use, coenzymes, metabolic regulation.